A One Step Method to Produce Boron Emitters. Issue 17 (24th April 2018) - A. Silva, José; Amaro e Silva, Rodrigo; Peral, Ana; del Cañizo, Carlos
Abstract : A one‐step method to obtain boron emitters for n‐type solar cells based on the use of boron tribromide (BBr3 ) as a dopant source is developed. During this study several experimental parameters are varied. It is observed that besides the diffusion temperature, the nitrogen gas flux and the BBr3 bubbler temperature have a significant impact on the obtained emitter properties. Using the adequate experimental conditions a homogenous boron emitter without boron rich layer (BRL), a sheet resistance of 77 Ω sq −1 and a dark saturation current <100 fA cm −2 is obtained. Abstract : A one‐step method to obtain boron emitters based on the use of boron tribromide as dopant source is here presented. The impact of the different experimental parameters on the emitters characteristics is analyzed. Using optimal experimental conditions, a homogenous boron emitter without boron rich layer, a sheet resistance of 77 Ω sq −1 and J 0e  < 100 fA cm 2 is obtained.